APPRAISAL OF REGULATORY FRAMEWORKS ON ENVIRONMENTAL PROTECTION POLICIES AND WASTE MANAGEMENT IN KWARA STATE, NIGERIA (Malaysian Management Journal, 2025)
Waste management has become a pressing global issue, requiring the enactment and enforcement of comprehensive regulatory frameworks to promote sustainability and protect the environment. Despite the available legislations, inadequate resources and inefficient monitoring impede their proper execution, allowing noncompliance and illicit trash disposal to continue. Illegal waste sites are popping up all over the city of Kwara in Nigeria. Improper garbage disposal appears to suggest a breakdown in the state's regulatory system for environmental protection and waste management. This paper has examined the regulatory framework of environmental protection policies and waste management in Kwara state. Both primary and secondary data were used. The population of the study was 280 and the sample size was 172, which was determined through a specific formula. A total number of 172 questionnaires were distributed to the selected respondents and from these 154 responses were retrieved. Findings from the study showed that the majority of the respondents disagreed that the regulatory frameworks did not prioritise the reduction, reuse, and recycling of waste materials. These respondents were of the view that there were clear guidelines and procedures for the proper handling and disposal of hazardous waste. The study also showed that the available regulatory frameworks have encouraged public participation and awareness of waste management practices in the state. Consequently, this paper has recommended that policymakers collaborate closely with communities to design strategies that incorporate local infrastructure, resources, and behaviours to reduce waste and promote recycling. There should also be frequent monitoring to ensure compliance. The rules and policies must be amended to ensure stakeholder engagement in waste management services.